War and Horror in Modern Spanish Theatre: The Sieges of Numantia and Saguntum as Lieux de Mémoire. - Balaskas, Vasileios (My University, 2023)
The sieges of Saguntum and Numantia have become legendary national landmarks in Spanish literary and artistic expression. The siege of Saguntum took place in 218 BCE, a battle between local Saguntines and Carthaginians, escalated into the Second Punic War and occurred near the modern Spanish city of Sagunto. It holds a symbolic place in the Spanish collective narrative as a heroic defense against invaders. Similarly, the siege of Numantia was considered a fragment of national history that exemplified collective sacrifice. The Celtiberian fortified settlement of Numantia, located near the modern Spanish city of Soria, had to defend its territory against the Roman Empire until death (134-133 BCE). According to national historiography and literature, Saguntum and Numantia were the two national battles in which the Spanish population collectively suffered the horrors of war. These battles showcased the fight of a nation against external invasions and demonstrated Spanish national unity against terror and death. Spanish literature appropriated these lieux de mémoire to create collective narratives. Miguel de Cervantes’ El Cerco de Numancia (1585) and José María Pemán’s and Francisco Sánchez-Castañer’s La Destrucción de Sagunto (1954) were repeatedly staged in the 20th century to showcase how war and death forged the Spanish identity. This paper analyzes how these tragedies used elements of military horror to showcase national suffering and sacrifice. In particular, the use of symbolic figures, such as sorcerers and personifications of Death and War, enhanced the dramatic power of the plays.
Ponencia en Congreso
Keywords: Teatro español - S. XX - Temas, motivos; Guerra en la literatura - España - S. XX; Lieux de Mémoire; Numantia; Saguntum; Theatre